2018
DOI: 10.1111/jcpe.12989
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations between acetylcholine levels and cholinesterase activity in saliva and gingival crevicular fluid and periodontal diseases

Abstract: Elevated acetylcholine levels and reduced butyrylcholinesterase activity are clinically associated with periodontal diseases and elevated levels of IL-17A and IL-17F. Therefore, non-neuronal cholinergic mechanisms may influence IL-17 biology and the aetiopathogenesis of periodontal diseases and therefore are possible therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
(82 reference statements)
2
15
0
1
Order By: Relevance
“…Furthermore, non‐parametric correlation analysis indicated that baseline ACh concentration and AChE activity levels correlated with MBL recorded at 1 month. This is in agreement with a previous study which demonstrated that ACh levels and esterase activity in saliva and gingival crevicular fluid correlated with alveolar bone loss in chronic periodontitis (Apatzidou et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, non‐parametric correlation analysis indicated that baseline ACh concentration and AChE activity levels correlated with MBL recorded at 1 month. This is in agreement with a previous study which demonstrated that ACh levels and esterase activity in saliva and gingival crevicular fluid correlated with alveolar bone loss in chronic periodontitis (Apatzidou et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we report for the first time that levels of ACh, This is in agreement with a previous study which demonstrated that ACh levels and esterase activity in saliva and gingival crevicular fluid correlated with alveolar bone loss in chronic periodontitis (Apatzidou et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations